Studying microbial pathogenesis and bacterial diseases. (June 2013) - Finlay, B Brett
B Brett Finlay speaks to Hannah Branch, Commissioning Editor B Brett Finlay is Professor in the Michael Smith Laboratories in addition to the Departments of Microbiology and Immunology, and Biochemistry and Molecular Biology at the University of British Columbia, Canada. He received a BSc (Honors) and a PhD (1986) in biochemistry at the University of Alberta, Canada. In 1989, he started work as Assistant Professor in the Biotechnology Laboratory at the University of British Colombia. He has focused his research on host–pathogen interactions at the molecular level. He has been at the forefront of the cellular microbiology field and contributed towards a number of important discoveries in this area while publishing over 400 manuscripts. Research in his laboratory is focused on, but not restricted to, Escherichia coli and Salmonella interactions with host cells. He is known across the globe for his research and has been honored with a number of prestigious awards, including the EWR Steacie Prize, the Canadian Society of Microbiology Fisher Scientific Award, a Medical Research Council scientist award, five Howard Hughes International Research Scholar Awards, a Canadian Institute of Health Research Distinguished Investigator award, British Columbia Biotech Innovation Award, the Michael Smith Health Research Prize, the Infectious Diseases Society of America Squibb award and the Jacob Biely Prize. He is a Fellow of the Royal Society of Canada and the Canadian Academy of Health Sciences, is an Officer of the Order of Canada, and is the University of British Columbia Peter Wall Distinguished Professor. He cofounded Inimex Pharmaceuticals, Inc. (BC, Canada), and is Director of the Severe Acute Respiratory Syndrome Accelerated Vaccine Initiative. He is also a valued member of several advisory and editorial boards, including that of Future Microbiology .